1982
DOI: 10.1111/j.1469-8986.1982.tb02495.x
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalograms in Children of Alcoholic Fathers

Abstract: The present study tested the hypothesis that 12-yr-old sons of alcoholic fathers will evidence an excess of fast EEG activity. Such sons have been shown to be at high risk for alcoholism. In this study, EEGs were recorded on a sample of 265 subjects who had been selected to maximize risk for deviant behavior (children of schizophrenics and children of psychopathic or character disordered parents) or selected as controls (children of normal parents). The sample included 27 children of alcoholic fathers and 258 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
1

Year Published

1986
1986
2005
2005

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(56 citation statements)
references
References 20 publications
3
52
0
1
Order By: Relevance
“…For example, increased theta power and theta/beta ratio is found in Attention Deficit Hyperactivity Disorder (Barry, Clarke, & Johnstone, 2003;Bresnahan & Barry, 2002;Chabot & Serfontein, 1996;Clarke, Barry, McCarthy, & Selikowitz, 2001;Clarke et al, 2003;Jasper, Solomon, & Bradley, 1938;Monastra et al, 1999;Satterfield, Cantwell, Saul, Lesser, & Podosin, 1973), and increased beta power is found in (a predisposition to) alcoholism (Ehlers & Schuckit, 1990, 1991Gabrielli et al, 1982;Propping, 1977;Rangaswamy et al, 2002;Van Sweden & Niedermeyer, 1999;Vogel, 2000). Therefore, understanding interindividual variance in EEG power could provide clues to the underlying neurobiology of these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased theta power and theta/beta ratio is found in Attention Deficit Hyperactivity Disorder (Barry, Clarke, & Johnstone, 2003;Bresnahan & Barry, 2002;Chabot & Serfontein, 1996;Clarke, Barry, McCarthy, & Selikowitz, 2001;Clarke et al, 2003;Jasper, Solomon, & Bradley, 1938;Monastra et al, 1999;Satterfield, Cantwell, Saul, Lesser, & Podosin, 1973), and increased beta power is found in (a predisposition to) alcoholism (Ehlers & Schuckit, 1990, 1991Gabrielli et al, 1982;Propping, 1977;Rangaswamy et al, 2002;Van Sweden & Niedermeyer, 1999;Vogel, 2000). Therefore, understanding interindividual variance in EEG power could provide clues to the underlying neurobiology of these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if one combines the results of most LR-HR EEG studies, thereby encompassing the slow alpha to fast beta frequency range, multiple scalp regions, and several EEG measures (9,14,15,26,35,48), the results document no risk group differences. However, in contrast, two studies (16,18) reported that at baseline, HR individuals have more fast activity (> 18 Hz) (18) and more fast alpha power (%12 Hz) (16) than LR individuals.…”
Section: Discussionmentioning
confidence: 97%
“…High risk Alcoholism Recovery function Auditory evoked potential INVESTIGATIONS into the electrophysiological differences between individuals at high risk for the development of alcoholism (high risk = HR) and matched, low-risk controls (low risk = LR) have frequently proceeded by comparing either baseline EEG activity (9,(14)(15)(16)18,26,35,48), the latency, morphology, and topography of event related potentials (ERPs) elicited by a variety of information processing paradigms [for reviews see (34,39)], or changes in each of these responses following an ethanol challenge (10,(14)(15)(16)26,27,35,38,39,48). The majority of ERP studies have evaluated the P300 component, and generally agree that P300 amplitude is reduced in HR individuals compared to LR individuals without an alcohol challenge [for reviews see (34,39)].…”
Section: Low Riskmentioning
confidence: 99%
“…Some investigators have found that EEG alpha and beta activity and event-related potentials (ERPs) are altered in subjects whose family history is positive for alcoholism (Begleiter et al, 1984;Ehlers & Schuckit, 1990;Elmasian, Neville, Woods, Schuckit, & Bloom, 1982;Gabrielli et al, 1982;Steinhauer, Hill, & Zubin, 1987). Other investigators have found no differences between FH-and FH+ subjects (Polich & Bloom, 1988;Whipple & Noble, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The weight of evidence that alcoholism is genetically transmitted combined with the electrophysiological differences that have been found between alcoholics and nonalcoholics have led to the search for a 3 Dis3t biological marker for alcoholism. In some studies when children of nonalcoholics (family history negative, FH-) have been compared with children of alcoholics (family history positive, FH+) they have revealed a significant difference in cognitive functioning and electrophysiological activity (Begleiter, Porjesz, Bihari, & Kissin, 1984;Drejer, Theilgaard, Teasdale, Schulsinger, & Goodwin, 1985;Gabrielli et al, 1982;Pollock et al, 1983).…”
Section: Introductionmentioning
confidence: 99%